Analisis Kejadian ISPA pada Anak di Puskesmas Sukaraya Kecamatan Baturaja Timur Kabupaten OKU Tahun 2021 - Chairi Atmaja; Erma Gustina; Dian Eka Anggreny (Jurnal Kesehatan Saelmakers PERDANA, 2022)
Acute respiratory infection (ARI) is still a major health problem and is the leading cause of death and mortality in the world, including in Indonesia. The purpose of this study was to describe the incidence of ARI. Methods This study uses a cross sectional design conducted at the Sukaraya Health Center, Baturaja Timur District, OKU Regency in August 2021 with a total sample of 104 respondents. The results of the bivariate analysis in this study obtained the mother's education variable p-value 0.555, knowledge p-value 0.000, mosquito venom use p-value 0.000, smoking p-value 0.932, history of breastfeeding p-value 0.011, ventilation p-value 0.005. The results of the multivariate analysis showed that the knowledge variable p-Value was 0.000 (<0.05) with OR=10,815. It can be said that there is a significant relationship between the use of mosquitoes, history of breastfeeding and ventilation with the incidence of ARI, while for the mother's education variable, there is no relationship related to the incidence of ARI. The more dominant variable in this study is the knowledge variable.